Constructal design for a clover-shaped high conductivity channel in a square heat generating body - Lingen Chen; Tian Xie; Fengyin Zhang; Huijun Feng; Yanlin Ge (Case Studies in Thermal Engineering)
Constructal design of a square heat generating body with a clover-shaped high thermal conductivity channel is carried out. The research focuses on minimizing the maximum temperature difference and the entropy generation rate by releasing degrees of freedom step by step. Through exploring the effects of thermal conductivity ratio and the proportion of high conductivity material area, which allows for a more nuanced understanding of how different design parameters affect the thermal performance and optimal construct. Results demonstrate that increasing these parameters significantly reduces temperature difference and thermodynamic irreversibility. For instance, when the thermal conductivity ratio rises from 100 to 600, the minimum dimensionless maximum temperature difference decreases by 28.1 %, and the minimum dimensionless entropy generation rate drops by 40.7 %. The study highlights the superiority of three degree-of-freedom optimization, which reduces the maximum temperature difference by 11.2 % and the entropy generation rate by 12.84 % compared to single degree-of-freedom optimization. Additionally, slender clover-shaped blades further improve heat transfer efficiency. The clover-shaped channel outperforms traditional I-shaped design and fan-shaped design, offering better thermal performance under the same conditions. The constructal design of clover-shaped high conductivity channel provides valuable insights for optimizing heat dissipation in electronic devices and other applications requiring efficient thermal management.